1989
DOI: 10.1002/srin.198900961
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of phosphorus and boron in austenite in Fe-10%Mn-P-B-alloys

Abstract: Equilibrium segregation of phosphorus at the grain boundaries of austenite has been studied in Fe–10%Mn–P–B‐alloys. The samples were equilibrated at temperatures of 750–1100°C and analysed after rapid quenching using Auger‐electron spectroscopy. The results show that boron markedly reduces segregation of phosphorus in austenite. Boron was also found to be segregated at the prior austenite grain boundaries. The intergranular boron concentration increases slightly with a rising austenitising temperature, but doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This value is similar to those derived from the segregation energy of boron (57-97 kJmol -1 ) using various experimental methods, such as SIMS, 31) autoradiography, 32) and the Auger-electron microscopy, 33) and is also similar to the value reported by Hondros. 20) If the molar volume of the austenite grain boundary, V m gb , is assumed to be 7.1 × 10 -6 m…”
Section: Effect Of Boron On the Grain-boundary Energy Ofsupporting
confidence: 89%
“…This value is similar to those derived from the segregation energy of boron (57-97 kJmol -1 ) using various experimental methods, such as SIMS, 31) autoradiography, 32) and the Auger-electron microscopy, 33) and is also similar to the value reported by Hondros. 20) If the molar volume of the austenite grain boundary, V m gb , is assumed to be 7.1 × 10 -6 m…”
Section: Effect Of Boron On the Grain-boundary Energy Ofsupporting
confidence: 89%
“…This is because in the site competition with phosphorus for segregation to GB, boron succeeds. Boron thus reduces P segregation in austenite . This is also the principle by which boron cleans the (austenite) GBs in medium Mn steels; Mn desegregates from the GBs owing to boron GB segregation and thus there is no GB embrittlement .…”
Section: Effect Of Boron On Toughness and Possible Mechanismsmentioning
confidence: 99%
“…P desegregation due to boron segregation to GB is in fact linear, as shown in the study by Liu et al, also shown in Figure . The free binding energy of boron segregation in austenite was estimated using AES to be −97, and −47 kJ mol −1 for phosphorus segregation . Morral and Jandeska Jr .…”
Section: Effect Of Boron On Toughness and Possible Mechanismsmentioning
confidence: 99%
“…[159] The fact that the addition of small amount of B suppresses phosphorus segregation at austenite grain boundaries suggests that B with a large free energy of segregation, presumably about 100 kJ/mol, affects segregation of phosphorus with a free energy of about 50 kJ/moi. [160,161] Therefore, the beneficial effect of adding B to the Nb-containing steel is considered in two respects: (i) enhancement of nucleation and growth of precipitates, in the precipitation temperature range, that leads to the depletion of carbonitride precipitants in the lattice, and (ü) depletion of strengthening elements, in the dissolution temperature range of precipitants, especially Nb, in the matrix owing to the non-equilibrium cosegregation of B and Nb to the grain boundary. The effect of B atoms in solute at grain boundaries can be viable in both of these scenarios.…”
Section: Effect Of Boron On Hot Ductilitymentioning
confidence: 99%